The Dynamics of Self-Actualization Among Working Women Pursuing Higher Education: A Phenomenological Study - Rahmanisa Murtaja Naswariski; Siti Rohmah Nurhayati (Pubmedia Social Sciences and Humanities, 2026)
This study aims to explore the meaning of self-actualization among women who simultaneously undertake the roles of worker and university student. Employing an interpretative phenomenological approach, the study involved four early adult women who were actively employed while pursuing higher education. Data were collected through semi-structured interviews and analyzed using reflective thematic analysis to identify the essence of participants’ lived experiences. The findings reveal that self-actualization is understood not as a final achievement but as an ongoing process of negotiation between professional demands, academic aspirations, and personal identity formation. Participants encountered challenges such as time conflicts, physical exhaustion, and emotional fluctuations, which were interpreted as integral to personal growth. Self-regulation, personal efficacy, and goal orientation emerged as central factors in sustaining commitment to capacity development. The study indicates that self-actualization among working women pursuing higher education is constructed through contextual, reflective, and adaptive processes, positioning it as an existential experience continuously negotiated within complex social circumstances.